PENGARUH KEKOMPAKAN TIM KERJA DAN KREATIVITAS TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA DI DINAS KOPERASI USAHA KECIL DAN MENENGAH KABUPATEN PASURUAN - Nuansa, Gilang; Sundjoto; Rahayu, Sri (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to examine the effect of Team Cohesion and Creativity on Employee Performance at the Cooperatives and Small and Medium Enterprises Office of Pasuruan Regency, both directly and through job satisfaction. The study population consists of 73 employees, all of whom were included in the sample using a census method. Data were analyzed using the Partial Least Square (PLS) approach with Smart PLS 3.0. The results show that: 1) Team Cohesion has a positive effect on employee performance, 2) Creativity has a positive effect on employee performance, 3) Team Cohesion has a positive effect on employee performance through job satisfaction, and 4) Creativity has a positive effect on employee performance through job satisfaction. These findings indicate that team cohesion and creativity have a significant contribution to employee performance, both directly and through job satisfaction.